Prevalence of antibodies to Leishmania infantum and Toxoplasma gondii in horses from the north of Portugal - Lopes, Ana Patrícia (BioMed Central, 2013)
BACKGROUND: Leishmania infantum and Toxoplasma gondii are protozoa with zoonotic and economic importance. Prevalences of antibodies to these agents were assessed in 173 horses from the north of Portugal. FINDINGS: Antibodies to L. infantum were detected by the direct agglutination test (DAT); seven (4.0%) horses were seropositive with DAT titres of 200 (n = 5), 800 (n = 1) and ≥ 1600 (n = 1). Antibodies to T. gondii were assayed by the modified agglutination test (MAT); 23 (13.3%) horses were seropositive with MAT titres of 20 (n = 13), 40 (n = 5), 80 (n = 3) and ≥ 160 (n = 2). No statistical differences were found among equine categories of gender (female, male and gelding), age (1.5–6, 7–12 and 13–30 years), type of housing (indoors and mixed/outdoors), ability (recreation, farming and sports) and clinical status (apparently healthy and sick) for both agents. CONCLUSIONS: Horses are exposed to and may be infected with L. infantum and T. gondii in the north of Portugal.